Synthetic CT‐aided multiorgan segmentation for CBCT‐guided adaptive pancreatic radiotherapy. Issue 11 (13th October 2021) - Dai, Xianjin; Lei, Yang; Wynne, Jacob; Janopaul‐Naylor, James; Wang, Tonghe; Roper, Justin; Curran, Walter J.; Liu, Tian; Patel, Pretesh; Yang, Xiaofeng
Abstract: Purpose: The delineation of organs at risk (OARs) is fundamental to cone‐beam CT (CBCT)‐based adaptive radiotherapy treatment planning, but is time consuming, labor intensive, and subject to interoperator variability. We investigated a deep learning‐based rapid multiorgan delineation method for use in CBCT‐guided adaptive pancreatic radiotherapy. Methods: To improve the accuracy of OAR delineation, two innovative solutions have been proposed in this study. First, instead of directly segmenting organs on CBCT images, a pretrained cycle‐consistent generative adversarial network (cycleGAN) was applied to generating synthetic CT images given CBCT images. Second, an advanced deep learning model called mask‐scoring regional convolutional neural network (MS R‐CNN) was applied on those synthetic CT to detect the positions and shapes of multiple organs simultaneously for final segmentation. The OAR contours delineated by the proposed method were validated and compared with expert‐drawn contours for geometric agreement using the Dice similarity coefficient (DSC), 95th percentile Hausdorff distance (HD95), mean surface distance (MSD), and residual mean square distance (RMS). Results: Across eight abdominal OARs including duodenum, large bowel, small bowel, left and right kidneys, liver, spinal cord, and stomach, the geometric comparisons between automated and expert contours are as follows: 0.92 (0.89–0.97) mean DSC, 2.90 mm (1.63–4.19 mm) mean HD95, 0.89 mm (0.61–1.36 mm) mean MSD, and 1.43 mm (0.90–2.10 mm) mean RMS. Compared to the competing methods, our proposed method had significant improvements ( p  < 0.05) in all the metrics for all the eight organs. Once the model was trained, the contours of eight OARs can be obtained on the order of seconds. Conclusions: We demonstrated the feasibility of a synthetic CT‐aided deep learning framework for automated delineation of multiple OARs on CBCT. The proposed method could be implemented in the setting of pancreatic adaptive radiotherapy to rapidly contour OARs with high accuracy.